SHORT-RANGE PRECURSORS OF THE DESTRUCTIVE GAZLI EARTHQUAKES - Sultankhodzhayev A.N.; Khusamiddinov S.S. (My University, 1988)
Continuous observations of those characteristics of natural fields that were identified as likely to be useful in forecasting are being made at a network of integrated prediction stations in the geodynamic survey areas of Uzbekistan. The data indicate that the short-range precursors of the Gazli earthquakes with the most pronounced anomalous changes were the intensity of anomalous electromagnetic emission (EME) and the concentration of randon. The authors' investigations indicate that the destructive Gazli earthquakes and their strongest aftershocks (M > 5) were preceded by a period in which similar, synchronous short-term precursor anomalies of EME and radon concentration (depending on the mechanism) could occur; the duration of the EME anomalies depends on M. The simultaneous appearance of anomalies in considerably different fields increases the probability that the event is a precursor.